GE_GERICHTE C/19000/2018 vom 26. Januar 2021 - GE Cour de justice (2021)
DIVORCE;SÉPARATION DE CORPS;MODIFICATION(EN GÉNÉRAL);OBLIGATION D'ENTRETIEN;CONJOINT;REVENU HYPOTHÉTIQUE;DÉBUT;MINIMUM VITAL | CC.118.al2; CC.179; CC.117; CC.125; CC.126